Gallium arsenide electronic materials and devices : a market and technology overview, 1999-2004. - Szweda, Roy (Elsevier Advanced Technology, 2000)
The third edition of this highly respected market study provides a detailed insight into the global developments of the GaAs industry to 2004, and the implications for both suppliers and users of GaAs technology. The report has been completely revised and updated with a new chapter added on competitive technologies. The report also supplies market analysis by component type and application sectors. For a PDF version of the report please call Tina Enright on +44 (0) 1865 843008 for price details.